Η ΠΡΟΣΛΗΨΗ ΤΗΣ ΑΡΙΣΤΟΤΕΛΙΚΗΣ ΕΝΝΟΙΑΣ ΤΗΣ ΕΠΙΕΙΚΕΙΑΣ ΣΤΗΝ ΠΟΛΙΤΙΚΗ ΣΚΕΨΗ ΤΟΥ ΜΑΡΣΙΛΙΟΥ ΤΗΣ ΠΑΔΟΒΑ ΚΑΙ Η ΠΟΛΙΤΙΚΗ ΚΑΙ ΚΟΙΝΩΝΙΚΗ ΠΡΑΓΜΑΤΙΚΟΤΗΤΑ ΣΤΗΝ ΠΑΔΟΒΑ ΣΤΟ ΜΕΤΑΙΧΜΙΟ 13ου ΚΑΙ 14ου ΑΙΩΝΑ - ΣΥΡΟΣ ΒΑΣΙΛΕΙΟΣ (Eoa kai Esperia, 2006)
This paper focuses on Marsilius of Padua’s notion of equity and the way itrelates to Aristotle’s doctrine of equity, as presented in the NicomacheanEthics. Our central aim is to place Marsilius into the broader context of thediscussions on the nature and importance of equity which took place in theLatin, Islamic, and Jewish philosophy of the Middle Ages. Marsilius viewsequity as complementary to law in cases that are not foreseen by the latter. Hethus considers equity as one of the desirable qualities of ideal ruler whichprovides him with guidance, especially with respect to his emotions, in caseswhere the law is deficient. In typical medieval fashion, Marsilius looks uponthe ruler as the highest judge inside the civil community whose primary taskconsists of the administration of justice. Equity is indispensable for the ruler’sfilling out the gaps left by law, yet the ruler has no right tampering with theexisting legal framework and attempting any modifications of it. He is theexecutive organ of the "legislator humanus", that means of the whole body ofthe citizens or the weightier part thereof, and has to follow consequently andenforce the laws made by the former, in order to avert civil strife and intestinedisturbances, and guarantee the inner stability and endurance the politicalcommunity. Marsilius highlights the functional aspects of equity in the sphereof justice. The ideal political community, as envisaged by Marsilius, presentsglaring analogies to Padua’s political organisation in the period of hercommunal government. As in Marsilius political theory, Padua’s podestà, thehighest executive organ of the commune, was obliged to act according to thestatutes of the city and could be punished or even deposed in case he violatedthem.